n-(-13)=-5

Simple and best practice solution for n-(-13)=-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n-(-13)=-5 equation:


Simplifying
n + -1(-13) = -5

Multiply -1 * -13
n + 13 = -5

Reorder the terms:
13 + n = -5

Solving
13 + n = -5

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + n = -5 + -13

Combine like terms: 13 + -13 = 0
0 + n = -5 + -13
n = -5 + -13

Combine like terms: -5 + -13 = -18
n = -18

Simplifying
n = -18

See similar equations:

| -7+-25= | | 1/a=8/7a-1/14 | | 0.5333=(136.779-35.9x)/(136.779-3.81x) | | 1.8+.03x=.17x-1 | | 4xy+3x-2y+5xy= | | 14y-9y= | | -4x+1=x+36-7 | | -4x+1=x+36-7 | | 5/(x+3)+10=15 | | 6(x-2)+3=5(2x+3) | | BC+V=3K | | 0.5333=(149.352-39.2x)/(149.352-3.81x) | | 36*x=9 | | 0.55=(150-40x)/(150-4x) | | (5x-8)=3 | | 2c*4e*5d= | | .3(x-2)+1=.25(x+9) | | 6*2x= | | 17+-17= | | -42+-24= | | 2m=-17 | | -3x=-49 | | 3g+11=67 | | a=(2,1) | | 4xsquared=49 | | 5k=57 | | 4n-14= | | x^2/64+12=x | | x^2-10x-5=10 | | 12-y=-15 | | (1/8)x^2-x+12=0 | | 2COS^2X+3SINX=0 |

Equations solver categories